Palladium‐Catalyzed Formal [4+2] Cycloaddition of Benzoic and Acrylic Acids with 1, 3‐Dienes via C—H Bond Activation: Efficient Access to 3, 4‐Dihydroisocoumarin and 5, 6‐Dihydrocoumalins. Issue 8 (31st May 2018) - Sun, Youwen; Zhang, Guozhu
Abstract: We report a palladium‐catalyzed formal intermolecular [4+2] cycloaddition of benzoic and acrylic acids with 1, 3‐dienes including the stock chemicals 1, 3‐butadiene and isoprene leading to synthetically useful 3, 4‐dihydroisocoumarins and 5, 6‐dihydrocoumalins. Stepwise C—H bond cleavage and annulation are likely involved in the reaction pathway. The synthetic potential of the methodology was demonstrated by two short derivatizations and total synthesis of natural product Clausamine B. Abstract : We report a palladium‐catalyzed formal intermolecular [4+2] cycloaddition of benzoic and acrylic acids with 1, 3‐dienes including the stock chemicals 1, 3‐butadiene and isoprene leading to synthetically useful 3, 4‐dihydroisocoumarin and 5, 6‐dihydrocoumalins. Stepwise C—H bond cleavage and annulation are likely involved in the reaction pathway. The synthetic potential of the methodology was demonstrated by two short derivatizations and total synthesis of natural product Clausamine B.